Disruption of Wnt production in Shh lineage causes bone malformation in mice, mimicking human Malik–Percin‐type syndactyly. Issue 3 (18th January 2018) - Zhu, Xiao‐Jing; Fang, Yukun; Xiong, Yanan; Wang, Min; Yang, Xueqin; Li, Yan; Zhang, Xiaoyun; Dai, Zhong‐Min; Qiu, Mengsheng; Zhang, Ze; Zhang, Zunyi
Abstract : Here, we show that Shh‐Cre ‐mediated deletion of Wntless, the Wnt cargo protein, in mouse posterior limb mesenchyme causes bone syndactyly of the 3rd and 4th digits, resembling the human Malik–Percin type. The Shh descendants gradiently distributed from digit 5 to posterior half of digit 3 in wild‐type limbs, however, they abnormally increased in posterior digit 3 in Wntless Shh‐Cre . Wntless Shh‐Cre limbs displayed altered expression of hedgehog pathway genes and impaired noncanonical Wnt signaling activity. We further showed that the anterior limb mesenchymal cells in the Wls Shh‐Cre served as a source of Wnt5a to reorientate the adjacent Wls ‐lacking Shh lineage cells to move anteriorly and subsequently led to syndactyly, suggesting that aberrant mesenchymal cell movement/condensation may underlie the pathogenesis of syndactyly. Abstract :